Application and progress of temperature-sensitive hydrogels in cartilage injury repair - Yu, Long; She, Kunhao; He, Rui; Xu, Qingyu (Frontiers in Bioengineering and Biotechnology, 2025)
Articular cartilage injury is an important challenge in the field of orthopedics. Due to its unique characteristics of being vascularless, neuralless, and without lymphoid tissue, as well as the poor proliferation and migration ability of chondrocytes, the self-repair ability of cartilage after injury is limited. In recent years, with the development of tissue engineering, temperature-sensitive hydrogels, a new type of biomedical material, have unique temperature-responsive phase transition characteristics (such as a phase transition critical point close to the physiological temperature) that enable them to rapidly form a stable three-dimensional porous structure triggered by body temperature after being injected into the joint cavity. The material is injectable, will form a gel in situ, and can construct a dynamic bionic extracellular matrix (ECM) microenvironment. Compared with chemically cross-linked hydrogels, this material can achieve precise spatiotemporal control without introducing exogenous stimuli, significantly reducing the risk of cytotoxicity. Through adjustable mechanical properties, highly efficient loading, and release of bioactive factors, as well as viscoelastic characteristics similar to natural cartilage matrices, it has shown great potential in the repair of articular cartilage injuries. This article reviews the research progress of temperature-sensitive hydrogels in the repair of articular cartilage injuries from aspects such as biological characteristics, mechanism of action, clinical applications, and challenges faced, providing new ideas and possibilities for cartilage injury repair.